Analisis Perbandingan Kedudukan dan Kewenangan Menteri dalam UUD 1945 Sebelum dan Sesudah Perubahan, Konstitusi RIS, dan UUDS RI - Josua Satria Collins (Jurnal Hukum Lex Generalis, 2020)
The Basic Law as the basic and highest law that contains the life of society, nation and state so that its nature must be more stable than other legal products. Especially if a Constitution contains the soul and spirit of a country that in the event of a change to the Basic Law can also bring a major and fundamental change to the system of implementation of a country. Even the wishes and aspirations of the people can also manifest in the constitution. In Indonesia itself, the constitution changes as the nation's historiography journeys. Starting from the formulation of the 1945 Constitution after independence, then changed to the Constitution of the United States of Indonesia, transformed back into the Provisional Constitution of 1950, until the re-enactment of the 1945 Constitution and the accompanying amendments. Theoretically, the change of the Constitution at least brings about changes in the structure of state government and the possibility is even further a change in the basis of state philosophy, state objectives, and state policy. This also applies to the system or concept of the Minister along with constitutional changes in Indonesia, which will be discussed further in this paper.